Relationship of Knowledge And Attitude of Nurses With Hand Hygiene Application Behavior - Dewi Selfiana; Hamdana; Hermadin; Haryanti Haris (Comprehensive Health Care, 2021)
The high rate of nosocomial infections is a very important problem in the hospital. Nurses' awareness to do hand hygiene is a fundamental behavior in an effort to prevent nosocomial infections that occur in hospitals. The research objective was to determine the relationship between knowledge and attitudes of nurses and the behavior of applying hand hygiene in the inpatient room at Lanto Dg Pasewang Jeneponto Hospital in 2020. This type of research design was creational with a cross-sectional research approach. The research population was 180 people. The sample was taken using purposive sampling with a total sample of 36 respondents. Data collection tools in the form of questionnaires and observation sheets. Based on the results of statistical tests using the fisher's exact test, the results of the p-value = 0.631> α = 0.05, so it can be concluded that there is no relationship between knowledge and the behavior of applying hand hygiene in the inpatient room of Lanto Hospital Dg Pasewang Jeneponto and for the relationship between attitude and behavior. The result obtained a p-value of 0.715> ɑ = 0.05, so it can be concluded that there is no relationship between attitude and behavior of applying hand hygiene in the inpatient room of Lanto Dg Pasewang hospital Jeneponto. Suggestions are expected that further researchers will expand the reach of the room/location.